Does vacuum delivery carry a higher risk of shoulder dystocia? Review and meta-analysis of the literature. (September 2016) - Dall'Asta, Andrea; Ghi, Tullio; Pedrazzi, Giuseppe; Frusca, Tiziana
Abstract: Introduction: Vacuum extractor has been increasingly used over the last decades and is acknowledged as a risk factor for shoulder dystocia (SD). In this meta-analysis we assess the actual risk of SD following a vacuum delivery compared to spontaneous vaginal delivery (SVD) and forceps. Materials and methods: Systematic literature search (English literature only) on MEDLINE, EMBASE, ScienceDirect, the Cochrane library andClinicalTrials.gov conducted up to May 2015. Key search terms included: Operative/Vacuum/Forceps delivery [Mesh] and shoulder dystocia and subheadings. 2 stage-process study selection. We included only studies where data concerning the occurrence of SD following operative vaginal delivery were reported as adjusted odds ratio (AOR) and no significant difference in confounding factors for SD was recorded. Included trials clustered according to the delivery mode (1) vacuum vs. SVD, (2) forceps vs. vacuum. Methodological quality of each study evaluated with the Newcastle–Ottawa System (NOS). Results: 87 potentially relevant papers. After applying inclusion and exclusion criteria only 7 were selected for the meta-analysis. Vacuum delivery appeared associated with a higher risk of SD than SVD in both fixed and random model (OR 2.87 and 2.98 respectively). No difference in the rate of SD was found between vacuum and forceps ( p > 0.05). Conclusion: Vacuum extractor carries an increased risk of SD compared with spontaneous vaginal delivery whereas the occurrence of SD does not seem to vary following vacuum or forceps.